Particularités du régime hydrochimique des eaux marines du sud du littoral roumain pendant la période décembre 1977 - novembre 1978 - Cociașu, Adriana; Popa, Lucia; Dorogan, Liliana (Cercetări Marine - Recherches Marines, 2026)
The paper presents some modifications in the seasonal dynamics of the main chemical agents having direct effects on the trophic potential of the sea in hydrological conditions specific to the period of December 1977 - November 1978.